2009
DOI: 10.1177/1074248409350138
|View full text |Cite
|
Sign up to set email alerts
|

Neither K + Channels Nor PI3K/Akt Mediates the Vasodilative Effect of Nebivolol on Different Types of Rat Arteries

Abstract: Nebivolol produced a concentration-dependent vasodilation in different rat arteries precontracted by PE or KCl. In the isolated rat aorta, carotid artery, femoral artery, and renal artery, neither K(+) channels nor PI3K/Akt pathway was involved in the relaxation induced by nebivolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…In this study, we demonstrate that nebivolol elicits marked dilation of both afferent and efferent arterioles. These findings are consistent with evidence obtained from whole kidney studies showing that nebivolol increased renal plasma flow (22,25), reduced renal perfusion pressure (22), and dilated renal arteries (16,17,47). At a dose of 1 mg/kg, estimated renal plasma flow increased significantly by 19%, while GFR increased 14% at this dose and 22% at 2 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we demonstrate that nebivolol elicits marked dilation of both afferent and efferent arterioles. These findings are consistent with evidence obtained from whole kidney studies showing that nebivolol increased renal plasma flow (22,25), reduced renal perfusion pressure (22), and dilated renal arteries (16,17,47). At a dose of 1 mg/kg, estimated renal plasma flow increased significantly by 19%, while GFR increased 14% at this dose and 22% at 2 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
“…However, some studies suggest that the cellular mechanisms of the vasodilator effect of nebivolol may also involve activation of the endothelial ␤ 2 -adrenoceptors (2,17,35), Ca 2ϩ -activated K ϩ channels (17) and P2Y-purinoceptor (26). It has also been suggested that while the vasodilation induced by nebivolol is mediated by endothelium-derived NO, ␤ 2, ␤ 3 -adrenoceptors, 5-hydroxytryptamine receptors (4), and K ϩ channels (47) are not involved in the nebivolol-induced vasodilation. These studies indicate the need for evaluating tissue specific responses thus necessitating our direct studies on the renal microvasculature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The antihypertensive activity of nebivolol, considered as a racemic combination of d-nebivolol and l-nebivolol (Scheen, 2001), depends on a dual mechanism of action: d-nebivolol is responsible for the selective of beta1 adrenergic receptors antagonism, while l-nebivolol is responsible for the vasodilatation via beta-2 adrenergic receptor antagonism, which leads to the peripheral systemic vascular resistance reduction, with a subsequent increase in the eNOS-dependent production of NO (Cockcroft et al, 1995;Waeber, 2000;Scheen, 2001;Cosentino et al, 2002;Münzel and Gori, 2009;Logeart and Solal, 2010). Thus, nebivolol is the unique beta adrenergic receptors blocker that improves NO availability causing vasodilatation in addition to its inhibitory effect on the heart (Wang et al, 2009). The antihypertensive effect of bisoprolol is attributed only to its cardioselective affinity of beta-1 adrenergic receptors, as it has not any vasodilator properties.…”
Section: Discussionmentioning
confidence: 97%